Kontribusi Power Lengan Terhadap Kemampuan Servis Bawah Bolavoli - Fuaddi, Fuaddi (UIR Press, 2018)
The aim of this study was to find out the contribution of arm muscles exploded toward underhand serviceskill of volleyball. This study was correlational design to determine the correlation between two variables which were arm muscles exploded as independent variable and volleyball service skill as dependent variable. The populations of this study were 14 extracurricular female students of SMP Negeri 6 Tambang, Kampar regency. The samples of this study were all of population. The instrument test was Two-Hand Medicine Ball Put, while service skill was tested by service skill test. From the correlation calculation result of product moment (r xy), it was found that r value (r xy) was 0.479. This positive value indicates that there is correlation between these two variables but the correlation level is not significant but medium.